Comparing the imitative skills of children and nonhuman apes - Malinda Carpenter; Josep Call (Revue de Primatologie)
We propose a framework which breaks down the mechanisms of social learning into their four constituent elements: actions, results, goals, and context. We review what is known about the use of each of these elements in children’s and apes’ social learning, with special attention to possible differences among apes with different rearing histories. We conclude that, by 12 months of age, human infants use each of the four elements when interpreting and selectively copying others’ behavior. Apes, on the other hand, appear to focus solely on the results of demonstrations (although there is some suggestive evidence that enculturated apes may copy actions and goals more than other apes). Finally, we show how these (and other related) findings can be explained by uniquely human skills and motivations for shared intentionality.